Repair of Humeral Shaft Nonunion With Plate and Screw Fixation and Iliac Crest Bone Graft. (August 2021) - Stevens, Nicole M.; Schultz, Blake J.; Lowe, Dylan T.; Egol, Kenneth A.
Abstract : Summary: A 58-year-old woman with a proximal 1/3 humeral shaft nonunion presented 2 years after initial injury. We present a technique for nonunion repair, including nonunion site preparation, direct compression of the fracture site using plate osteosynthesis, and iliac crest bone graft harvest and utilization. The purpose of this video is to review humeral shaft nonunion literature and describe our management technique.